EFFECT OF AMBON BANANA (Musa acuminata) PEEL EXTRACT AS TEETH WHITENING AGAINST KINTAMANI COFFEE STAIN - Giri, Putu Ratna Kusumadewi; Rahaswanti, Luh Wayan Ayu; Kristanto, Riki; Nitha Dewi, Desak Ayu Dhyana (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: Tooth discoloration can impair the aesthetic function of teeth, leading to an increased demand fordental treatments, especially teeth whitening procedures. Teeth whitening with chemicals can cause negativeimpacts such as gingival irritation and tooth sensitivity. Natural ingredients can be used such as ambon banana(Musa acuminata) peel which contains saponins, which are bioactive compounds that can whitening teeth.Purpose: The purpose of this study was to determine the effect of ambon banana peel extract as a natural toothwhitening agent on external staining using robusta kintamani coffee. Methods: This type of research isexperimental laboratory study using 36 samples of upper and lower jaw permanent teeth. Each categorizedsample was immersed in a coffee solution for 12 days to evaluate the color changes that occour. Treatment groupwas immersed in ambon banana peel extract, control group was immersed in 10% carbamide peroxide. Eachgroup was observed every 3 hours for 5 days. Tooth discoloration was measured using vitapan classicalshadeguide. Results: The result show that the highest mean value of tooth color change occurred in the samplegroup immersed with ambon banana peel extract which reached 7.42, with p value <0.05 that indicated asignificant difference. Conclusion:It can be conclude that Ambon banana peel extract (Musa acuminata) is aneffective extract for teeth whitening after immersion with Kintamani robusta coffee.Keywords: Ambon banana peel extract, Carbamide peroxide 10%, Robusta kintamani coffe, Tooth discoloration.